PERAN TEKNOLOGI INFORMASI DALAM ADMINISTRASI PENDIDIKAN AGAMA ISLAM - ZAKIAH, NENG ISMI SALMA (LPPM STAI Al-Azhary Cianjur, 2024)
This study delves into the role of information technology in Islamic Religious Education (PAI) administration. With the rapid advancement of technology, the incorporation of information technology in educational administration is increasingly crucial to enhance the efficiency and effectiveness of learning and educational management processes. Employing a qualitative approach and literature review methods, this research examines various literature and previous studies related to information technology application in PAI administration. The findings reveal that information technology significantly simplifies information access, expedites administrative processes, and enhances the quality of educational services. Furthermore, information technology facilitates educational material dissemination, student data management, and communication among teachers, students, and parents. Despite challenges such as infrastructure limitations, educators' technical capabilities, and data security concerns, the study concludes that effectively implementing information technology in PAI administration can yield substantial positive impacts with the support of all relevant stakeholders.